Endothelial Jak3 expression enhances pro-hematopoietic angiocrine function in mice - José Gabriel Barcia Durán (Nature Portfolio, 2021)
Barcia Durán et al. show that the tyrosine kinase gene Jak3 is expressed in multiple endothelial cell types in the mouse, including in non-hematopoietic organs, with particularly high expression in the bone marrow. Using mice lacking Jak3, they show that Jak3 expressed in the bone marrow niche is important for maintaining long-term repopulating hematopoietic stem cells.